The Operation Car Wash in Folha de S.Paulo - Mércia Alves; Bernardo Geraldini (Íconos)
This article aims to understand how the Operation Car Wash was portrayed in the editorials of Folha de S.Paulo, one of the most influent Brazilian newspapers. Due to the importance of the operation in the current political scenario, we examine the newspaper’s stance in relation to the operation and the actors involved in it. We analyzed the thematic agenda, the actors involved, and the main framings employed in the editorials published in 2014 and 2015. Regarding politicians, we noted that the newspaper focused on individuals associated with the Brazilian Workers’ Party. In terms of framings, the main ideas conveyed were that 1) the operation signaled a greater maturity than the institutions in control; and 2) politicians exploited the State to their own (and their parties’) benefit.